Interactions between the Interpretation of Article 10 ECHR and the EU Directive on the Protection of Whistleblowers - Górski, Marcin (Towards a Better Protection of Workplace Whistleblowers in the Visegrad Countries, France and Slovenia, 2021)
This chapter presents the evolution of the Strasbourg case-law concerning the protection of whistleblowers, starting from the 2008 Guja v. Moldova judgment, and confronts the EU Directive’s provisions on public disclosure with the ECtHR’s relevant standard of interpretation of Article 10 of the Convention (the Guja’s six-element test). The work concludes that there exist certain divergencies between the Convention standard and Article 15 of the Directive and that somewhat confusing wording of the latter provision is likely to cause future interpretative malfunctions if one employs only grammatic interpretation of that provision while forgetting about the general function and scheme of the Directive.